Pengawasan Satuan Polisi Pamong Praja dalam Penerapan Peraturan Daerah kabupaten Indragiri Hilir No.5 Tahun 2016 tentang kawasan Tanpa Rokok di Kota Tembilahan - Reza, Reza Fahlevi (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
This research aims to determine the efforts made by the Civil Service Police Unit in monitoring and enforcing Regional Regulation Number 5 of 2016 concerning No-Smoking Areas in the District. Inhil, the results of the Implementation of Supervision of Regional Regulation Number 5 of 2016 concerning Non-Smoking Areas in the District. inhil carried out by the Civil Service Police Unit. To achieve this goal, researchers used data collection techniques through interviews and documentation. This research uses a qualitative approach and the type of research is a case study. The data analysis technique used is non-statistical technical, namely descriptive. The data obtained from the research results were processed using qualitative descriptive analysis. Research results show that: 1) efforts made by the Civil Service Police Unit in Enforcement of Regional Regulation No. 5 of 2016 concerning No-Smoking Areas, namely guidance in the form of direct outreach by visiting locations of non-smoking areas and giving advice to the public not to smoke in areas where smoking is prohibited and establishing cooperation with relevant government agencies and supervisors 2) Results of the Implementation of Enforcement of Regional Regulation No. .5 of 2016 regarding smoking-free areas carried out by the Civil Service Police Unit, namely increasing public knowledge about smoking-free areas, increasing public awareness to comply and more and more private agencies inviting cooperation to create smoke-free areas. cigarettes while the results of monitoring efforts carried out 3) Obstacles Faced by the Civil Service Police Unit in Enforcing Regional Regulation Number 5 of 2016 concerning No-Smoking Areas in the District. The bottom line is that there are still many SPG Cigarettes that are not marketing on target and external obstacles from Satpol PP are that the public is not aware of the regional regulations on non-smoking areas and there is still a lack of public awareness to comply with the rules. Apart from that, there are still many government agencies that do not have smoking rooms